Second messenger/signal transduction pathways in major mood disorders: moving from membrane to mechanism of action, part I: major depressive disorder - Niciu, Mark J. (CNS Spectr, 2013)
The etiopathogenesis and treatment of major mood disorders have historically focused on modulation of monoaminergic (serotonin, norepinephrine, dopamine) and amino acid [γ-aminobutyric acid (GABA), glutamate] receptors at the plasma membrane. Although the activation and inhibition of these receptors acutely alter local neurotransmitter levels, their neuropsychiatric effects are not immediately observed. This time lag implicates intracellular neuroplasticity as primary in the mechanism of action of antidepressants and mood stabilizers. The modulation of intracellular second messenger/signal transduction cascades affects neurotrophic pathways that are both necessary and sufficient for monoaminergic and amino acid–based treatments. In this review, we will discuss the evidence in support of intracellular mediators in the pathophysiology and treatment of preclinical models of despair and major depressive disorder (MDD). More specifically, we will focus on the following pathways: cAMP/PKA/CREB, neurotrophin-mediated (MAPK and others), p11, Wnt/Fz/Dvl/GSK3β, and NFκB/ΔFosB. We will also discuss recent discoveries with rapidly acting antidepressants, which activate the mammalian target of rapamycin (mTOR) and release of inhibition on local translation via elongation factor stimulation. Throughout this discourse, we will highlight potential intracellular targets for therapeutic intervention. Finally, future clinical implications are discussed.